Traditional Markets in Pekalongan City: Imam Al-Ghazali’s Perspective and SWOT Analysis Construction - Muhammad Khoirul Fikri; Rizky Andrean (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This study aims to find out how traditional markets in Pekalongan Regency are from the perspective of Imam Al-Ghazali and the construction of SWOT analysis. This research is qualitative research that combines field studies and literature studies. The data in this study were obtained from interviews, observations, documentation, and also literature reviews such as books, journals, and other sources that are considered credible and relevant to the research topic. The results of the study show that the existence of traditional markets is very important for the people of Pekalongan Regency, both from the perspective of traders and buyers. Traditional markets have become a place for some people to find a source of livelihood. And for some other people, traditional markets are places to get various goods they need. This is following Imam Al-Ghazali’s thoughts about the importance of the market and the economic system in it. However, from a practical point of view, there are also things in traditional markets that are not following Imam Al-Ghazali’s thoughts. In the construction of SWOT analysis, traditional markets have various strengths, weaknesses, opportunities, and challenges that will affect their existence and development.